Overview of brain health and dental caries in early childhood in Pekon Wonodadi, Gadingrejo Subdistrict, Pringsewu Regency - Arianto, Arianto; Purnomowati, RR Ratnasari Dyah; Muliadi, Muliadi; Linasari, Linasari (Riset Informasi Kesehatan, 2025)
Background: Dental caries is the destruction of tooth tissue that begins at the surface and can progress to the pulp (Nurhidayanti, 2020). According to the 2018 Basic Health Research (Riskesdas), the most common dental problem in Indonesia is decayed/damaged/aching teeth (45.3%), with an average DMF-T index of 1.9 for permanent teeth. Caries experience frequently occurs among elementary school children, particularly when dental care habits are poor. Brain health plays a vital role in children’s learning abilities, especially in fifth grade, when brain development accelerates and affects cognitive functions such as concentration. A study by Kusmana and Restuningsih (2020) showed a relationship between the DMF-T index and students’ academic performance.This study aims to describe brain health and def-t (decayed, extracted, and filled teeth in primary teeth) among early childhood children in Pekon Wonodadi, Pringsewu. Method: This research used a descriptive survey method. The population included all early childhood children using total sampling, with data collected through questionnaires and def-t examination forms.. Results: The study found that the majority of parents were adults (83%), and 65% of them were housewives. Good brain health was observed in 74.7% of the children, while a high prevalence of dental caries (def-t) was found in 80.6% of them. Conclusion: This study can help identify early childhood children who are at high risk of brain health issues and dental caries, supporting early intervention efforts.